Morphology of the eye and surrounding structures of the bowhead whale, Balaena mysticetus - Zhu, QA; Hillmann, DJ; Henk, WG (2001)
Observations were made on eyes from 46 bowhead whales, Balaena mysticetus, taken in the subsistence harvest near Barrow, Point Hope, Savoonga, and Kaktovik, Alaska. Data reported here include palpebral, eyeball, corneal, scleral, pupillary, and lens dimensions. These quantitative data have allowed us to compare structures relative to one another and sometimes to compare them with similar structures in other species. We found, for example, that the cornea is almost three times as thick at its periphery as at its center; that when the ratio of scleral thickness and eyeball size are compared, the ratio, in the bowhead whale, is twice that of any other cetacean for which data were available; and that the corneal and pupillary width to height ratios indicate a less elongated cornea and pupil than has been reported in other cetaceans. We also found a strong correlation between body length and eyeball size indicating that within the species, unlike what is seen between species, larger animals have larger eyes. Novel observations include the presence of three periorbital fatty layers, 112 ciliary processes, the presence of scleral canals, the absence of an obvious fovea or macular region in the retina, a holangiotic pattern of fundic vessels, the presence of zonular fibers and a lens sheath, and the absence of arl obvious pupillary operculum. Anatomical features like the wide angle of divergence and the palpebral dimensions suggest the absence of binocular vision while features like the size of the palpebral sac, abundant conjuctival fat, and the prominence of the retractor bulbi muscle suggest mechanisms for the protrusion and retraction of the eyeball.